PENTINGNYA PENGURUSAN HAK KEKAYAAN INTELEKTUAL BAGI PRODUK-PRODUK LITBANGYASA - Dewi Anggraeni (Jurnal Surya Kencana Dua : Dinamika Masalah Hukum dan Keadilan, 2016)
This intellectual property is the result of a thought to carry away or human creativity that produced a work in art, literature, science and technology in it that has economic benefits, so it's important for an invention that has no economic benefit can not be regarded as a (Intellectual Property). The importance of registration of intellectual property rights in research institutes, development and Engineering (Litbangyasayasa) to determine the extent of the competence centers Litbangyasayasa researchers understand and apply patent. Already generally familiar with patents, but technical understanding will term patent protection, the invention criteria can obtain a patent is still relatively lacking. Most researchers conducted research on the basic job of the boss, do not indicate the seriousness of the invention to produce something new and inventive contain elements or lack of awareness on the importance of applying for registration of an invention.Keywords: Intellectual Property Rights, Products Litbangyasa